Sistem Informasi Pelayanan Pembuatan Surat Keterangan Catatan Kepolisian (SKCK) Pada Polsek Jiput Menggunakan Metode Prototype - nurul Hidayat; Ayu Mira; Andrianto (Fakultas Teknologi dan Informatika, 2023)
Jiput Police, Pandeglang Regency is a community service sector in the legal area of Jiput District. Based on the development of the Jiput Police, the National Police always tries to improve its services to the community, especially in the field of security and public order. The police carry out repetitive activities because the system used still relies on agenda books which are not integrated with the database, thereby slowing down performance in services to citizens. This system was designed using Flow Of System (FOS), Context Diagram, Data Flow Diagram (DFD), Entity Relationship Diagram (ERD) and uses the PHP programming language, Sublime Text, XAMPP, and MySQL database. This information system was created to simplify police services, so that with this system it can be recorded in a computerized database